Solenodon paradoxus (Soricomorpha: Solenodontidae). (30th December 2015) - Derbridge, Jonathan J.; Posthumus, Erin E.; Chen, Hsiang Ling; Koprowski, John L.
Abstract: Solenodon paradoxus Brandt, 1833, is a large lipotyphlan insectivore commonly called the Hispaniolan solenodon. S. paradoxus is 1 of 2 extant species in the genus Solenodon, and 2 subspecies are recognized. The species is one of few venomous mammals with venom delivery through a channel in a modified lower incisor. Current distribution is limited to the Dominican Republic and southern Haiti. S. paradoxus is listed as "Endangered" by the International Union for Conservation of Nature and Natural Resources; threats to conservation include habitat loss, fragmentation, and degradation, predation by exotic carnivores, and persecution from farmers.